Stakeholders' views on online interventions to prevent common mental health disorders in adults implemented into existing healthcare systems in Europe. (7th July 2021) - Kuso, Stefanie; Nitsch, Martina; Zeiler, Michael; Simek, Monika; Adamcik, Tanja; Dey, Michelle; Berger, Thomas; Krieger, Tobias; Weisel, Kiona K; Zarski, Anna-Carlotta; Ebert, David D; Schaub, Michael P; et al.
Abstract: Background: Online preventive interventions can help to reduce the incidence of mental disorders. Whereas knowledge on stakeholders' attitudes and factors relevant for successfully integrating online treatment into existing healthcare systems is available, knowledge is scarce for online prevention. Methods: Stakeholders from Germany, Switzerland, Austria and Spain were surveyed. Potential facilitators/delivery staff (e.g. psychologists, psychotherapists) completed an online questionnaire ( n = 183), policy makers (i.e. from the governing sector or health insurance providers) participated in semi-structured interviews ( n = 16) and target groups/potential users of mental illness prevention ( n = 49) participated in ten focus groups. Thematic analysis was used to identify their experiences with and attitudes and needs regarding online programmes to prevent mental disorders. Additionally, it was examined which groups they consider underserved and which factors they consider as fostering and hindering for reach, adoption, implementation and maintenance (cf. RE-AIM model) when integrating online prevention into existing healthcare systems. Results: Main advantages of online mental illness prevention are perceived in low structural and psychological barriers. Lack of personal contact, security, privacy and trust concerns were discussed as disadvantages. Relevant needs are high usability and target group appropriateness, evidence for effectiveness and the use of motivational tools. Conclusions: Positive attitudes among stakeholders are the key for successful integration of online mental illness prevention into existing healthcare systems. Potential facilitators/delivery staff must receive training and support to implement these programmes; the programmes must be attractive and continuously evaluated, updated and promoted to ensure ongoing reach; and existing infrastructure and contextual factors must be considered.